Die nier- en nierpoortmorfologie van Geochelone pardalis (Chelonia: Testudinidae) - De Lange, P. C.(Pietro Cornelia) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1984.